P209 Chest wall tuberculosis presentations in east london. (12th November 2019) - Pang, DX; Skyllberg, E; Sundaralingam, A; Rahman, A; Burman, M; Tiberi, S; Kunst, H
Abstract : Introduction: Tuberculous abscesses are rare, accounting for 1% of extra-pulmonary tuberculosis (TB). The chest wall is often a site for cold abscesses. There have been only case reports described in the literature. We report a case series of chest wall TB diagnosed in a large European centre. Methods: A retrospective analysis of at a large European centre of all TB cases between 2005 -2018 notified in the London TB register. Results: We identified 22 cases of chest wall TB, this was 0.3% of all TB cases over this time period. 81.8% (18/22) were male, the median age was 33.06 years (SD 14.05 years). 81.8% (18/22) were of Asian ethnicity. 31.8% (7/22) had concurrent pulmonary TB whilst 22.7% (5/22) had concurrent osteomyelitis, of these 60% (3/5) had osteomyelitis of the spine. 81.8% (18/22) were M.TB culture positive, with just 5.5% (1/18) who had resistant disease (to Streptomycin and Isoniazid). In 71% (15/21) of cases we were able to demonstrate granulomatous inflammation on histology. 95.4% (21/22) received 6 months of treatment. All patients completed their treatment successfully and no relapses were recorded, no patient required surgery. Conclusion: The diagnosis of chest wall TB can be challenging but should be considered in an at-risk population. Microbiological diagnosis is highly attainable and will help guide treatment. Prompt diagnosis and treatment is important in preventing additional complications, often in the form of osteomyelitis.